(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To compare the results of lung isolation between the bronchial blocker and the double-lumen tube in patients with esophageal tumor surgery. Subjects and methods: Descriptive, clinical intervention, controlled, prospective study with patients ≥ 18 years old, ASA I-III, undergoing endoscopic esophageal tumor resection, with indications for one-lung ventilation at Viet Duc University Hospital from June 2024 to June 2025. Results: There were 64 patients divided into 2 groups bronchial blocker and double-lumen tube. Characteristics of the study group and preparation time and one-lung ventilation time without preparation time of the difference between the two groups was not statistically significant. However, there was a significant difference in surgeon satisfaction with the bronchial blocker group (1.88 ± 0.34 points) compared with the double-lumen endotracheal tube group (1.31 ± 0.47 points) with p < 0.05. Conclusion: One-lung ventilation using a bronchial blocker or a double-lumen endotracheal tube both had good surgical fields in endoscopic surgery for esophageal resections. However, the advantage belonged to bronchial blocker in terms of surgeon satisfaction. On the contrary, double-lumen endotracheal tube showed superiority in mechanical stability, suitable for more in long surgeries and requiring continuous stability.